2016
DOI: 10.19082/3138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Folic Acid therapy on Homocysteine Level in patients with Atherosclerosis or Buerger’s Disease and in Healthy individuals: A clinical trial

Abstract: BackgroundHyperhomocysteinemia is considered a risk factor for atherosclerosis and some other vascular diseases such as Buerger’s disease.ObjectiveThe aim of this study was to measure the Homocysteine levels in 3 different groups of participants (Buerger’s disease, atherosclerosis patients, and healthy cases) and determine the therapeutic effect of folic acid therapy on homocysteine levels for these three groupsMethodsThis nonrandomized clinical trial study was conducted in the vascular and endovascular surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In clinical studies, low serum folate levels were associated with a more severe disease [ 36 ]. Homocystine is a predictor of radiological progression of COVID-19 [ 37 ] Folic acid supplementation also reduces the level of homocystine [ [38] , [39] , [40] ]. In in-silico studies, folic acid was also found to bind to active site of coronavirus main proitease [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In clinical studies, low serum folate levels were associated with a more severe disease [ 36 ]. Homocystine is a predictor of radiological progression of COVID-19 [ 37 ] Folic acid supplementation also reduces the level of homocystine [ [38] , [39] , [40] ]. In in-silico studies, folic acid was also found to bind to active site of coronavirus main proitease [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, FA with or without vitamin B12 given for 30 days could prevent mitochondrial dysfunction and DNA damage caused by short-term treatment with arsenic trioxide in rats (Majumdar et al 2009). FA treatment in stressed rats was able to reduce depressive-like behaviors and brain oxidative damage, and ameliorate hippocampal antioxidant imbalance (Budni et al 2013;Réus et al 2018;Menegas et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Still, some are unable or unwilling to quit smoking. Additionally, medical therapy with antiplatelets, calcium channel blockers for associated vasospasm, folic acid for concurrent hyperhomocysteinemia, 7 as well as suitable analgesics for pain reduction, and appropriate antibiotics for superimposed infection are also administered. No further measure is indicated, unless CLI with disabling rest pain or tissue loss develops.…”
Section: Discussionmentioning
confidence: 99%